Supermasi Model Kooperatif Tipe Numbered Head Together dan Snowball Throwing terhadap Motivasi Belajar Siswa - Amiruddin, Ibnu (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2024)
This study aims to determine students' learning motivation using the cooperative learning model type Numbered Head Together (NHT) and cooperative type snowball throwing on basic competency standards explaining the analysis of information conveyed through advertisements from print or electronic media at MINU Terate Putra Gresik. This study uses the type of Quantitative Research. Collecting data in this study using observations and questionnaires obtained through the observations of researchers and questionnaires distributed to students. The procedures in this research, namely the preparation and research planning stages, implementation stages, and final stages. From the results obtained, it shows that: There is a comparison of student learning outcomes in the Experiment class using the NHT type cooperative learning model with student learning outcomes in the Control class using the snowball throwing type cooperative model. This is due to the effect of Cooperative Type Numbered Head Together (NHT) with the results of .042 < 0.05 and tcount 2.202 > 2.110 then a significant effect is obtained and the Cooperative Type of snowball throwing shows the results of X2 (Snowball Throwing) on Y (Learning Motivation) of 0.001 < 0.05 and tcount of 4.404 > 2.110.